Banking on the poor - Abd Razak, Dzulkifli (2007)
developing a bank for the poor — the Grameen Bank. Muhammad Yunus, in his acceptance speech delivered on Dec 10, in Oslo, described the prize as the highest honour and dignity accorded to the hundreds of millions of women all around the world who struggle every day to make a living and bring hope for a better life for their children. It was a historic moment not only for them but for all those who work and feel for the poor everywhere. Indeed, Malaysia was one of the first to recognise Yunus and his early work, through his association with Universiti Sains Malaysia. It goes back to 1986 when Yunus was part of the steering committee for "Projek Ikhtiar", an applied research project based at the university.